2020
DOI: 10.1155/2020/6126490
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-17~92 Cluster Ameliorates High Glucose-Induced Podocyte Damage

Abstract: The loss and damage of podocytes is an early feature of diabetic nephropathy (DN). The miR-17∼92 cluster was dysregulated in diabetic and polycystic kidney disease patients, but its role in DN is unclear. Hence, an in vitro study on the high glucose- (HG-) treated mouse podocytes (MPC5) was designed to elucidate the effect of miR-17∼92 cluster downregulation on cell viability, apoptosis, inflammation, fibrosis, and podocyte function. The results suggested that the miR-17∼92 cluster members miR-17-5p, miR-18a, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…After that, we established that lnc‐H19/miR‐20a levels were correlated with TGFβ/Smad pathway activity (Figure 5D). The anti‐fibrotic effect of miR‐20a was reported in pulmonary, 38 cardiac, 39 and kidney 40 fibrosis. In this study, artificially up‐regulated and down‐regulated miR‐20a could, respectively, inhibit and promote the levels of fibrotic and mesenchymal markers (Figure 4A,B), suggesting that miR‐20a might be an inhibitor for skeletal muscle fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…After that, we established that lnc‐H19/miR‐20a levels were correlated with TGFβ/Smad pathway activity (Figure 5D). The anti‐fibrotic effect of miR‐20a was reported in pulmonary, 38 cardiac, 39 and kidney 40 fibrosis. In this study, artificially up‐regulated and down‐regulated miR‐20a could, respectively, inhibit and promote the levels of fibrotic and mesenchymal markers (Figure 4A,B), suggesting that miR‐20a might be an inhibitor for skeletal muscle fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports suggested that miR-17-5p is highly expressed in the renal biopsy tissues of patients with DN patients as well as in high glucose-treated mouse podocytes, 18 and upregulated miR-17-5p significantly accelerates cell apoptosis in podocytes treated with high glucose. 31 However, the role of miR-17-5p in high glucose-treated MCs is yet unknown.…”
Section: Inhibition Of Mir-17-5p Activates Wnt/β-catenin Signaling In Hmcs By Upregulating Kif23 Expressionmentioning
confidence: 92%
“…MiR-17-5p is a member of the miR-17~92 cluster that was shown to be highly expressed in the renal biopsy tissues of patients with DN patients as well as in high glucose-treated mouse podocytes. 18 Previous study indicated that the occurrence of gestational diabetes is related to increased expression of miR-17-5p. 19 Additionally, miR-17-5p was reported to be responsible for insulin sensitivity and glucose homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature [ 26 ], after the recovery, passage, and differentiation of MPC5 cells, the cells were grouped as follows: (1) NG group (Normal glucose), MPC5 cells were cultured in RPMI 1640 medium supplemented with 5.5 mM glucose for 48 h; (2) HG group, MPC5 cells were cultured with 25 mM glucose in RPMI 1640 medium for 48 h, and the concentration of HG was determined as per the reference [ 27 ]; (3) HG + TP group, MPC5 cells were cultured with 25 mM glucose and 10 uM TP in RPMI 1640 medium for 48 h, and the administration method and dosage of TP were referred to a previous study [ 10 ]. (4) HG + IRB group, MPC5 cells were cultured in RPMI 1640 medium supplemented with 25 mM glucose and 10 uM irbesartan for 48 h, with irbesartan used as a positive control.…”
Section: Methodsmentioning
confidence: 99%